Passively Q-Switched pulse erbium doped fiber laser using Antimony (III) Telluride (Sb2Te3) thin film as saturable absorber - Zalkepali, Noor U.H.H.; Awang, Noor Azura; Yuzaile, Yushazlina R.; LATIF, Amirah A.; Ahmad, Fauzan; Azmi, A N; Abdul Hadi, Fatin Shaqira; Zakaria, Zahariah (Science Publishing Corporation, Publisher of International Academic Journals, 2018)
This paper demonstrates on an antimony telluride (Sb2Te3) thin film sandwiched between two fiber ferrule as saturable absorber for Qswitched pulsed Erbium doped fiber (EDF) laser. The saturable absorber is fabricated by dissolving Antimony (III) Telluride powder into PVA solution and dry in the ambient temperature for 48 hours. Then, 1 mm2 x 1 mm2 Sb2Te3-PVA film based saturable absorber is sandwiched in between FC/PC ferrule for Q-switched laser generation. The modulation depth of the Sb2Te3 is measured as 28.01% with input intensity 0.02 MW/cm2 . The developed passive saturable absorber integrated in EDF laser in ring cavity and the characterised pulse is with repetition rates of 30.21 kHz, shortest pulse width of 3.26 µs and signal-noise-ratio (SNR) of 42 dB. The maximum output pulse energy is achieved at pump power 69.5 mW with 29.5 nJ and the output power 0.89 mW.